Pelaksanaan Pembelajaran Akuntansi Kelas XI A1 Pada SMKN-1 Katingan Hilir - Sundari, Siti; Suyati, Endang Sri (Neraca: Jurnal Pendidikan Ekonomi, 2017)
This study aims to find out how the implementation of accounting learning, the subject under study is Vocational High School 1 Katingan Hilir. This study uses qualitative methods with descriptive research types, which are the subjects of this study are principals, accounting teachers, and students. Accounting class XI and Class XII are still referring to the KTSP curriculum, some important points obtained are: 1) the teacher prepares lesson plans as direction in the implementation of accounting learning activities, 2) pray before starting the lesson, 3) attend students, 4) identification of learners ’needs, 5) material delivered by using methods in carrying out competency examination assignments in each student’s accounting book, 6) evaluating the achievement of students’ learning goals consisting of skills in working on problems, neatness and accuracy. Based on the results of research found in the field that the implementation of accounting learning has not been maximal and the applied accounting subjects have not run optimally.